Compound heterozygosity for loss‐of‐function FARSB variants in a patient with classic features of recessive aminoacyl‐tRNA synthetase‐related disease. Issue 6 (10th April 2018) - Antonellis, Anthony; Oprescu, Stephanie N.; Griffin, Laurie B.; Heider, Amer; Amalfitano, Andrea; Innis, Jeffrey W.
Abstract: Aminoacyl‐tRNA synthetases (ARSs) are ubiquitously expressed enzymes that ligate amino acids onto tRNA molecules. Genes encoding ARSs have been implicated in phenotypically diverse dominant and recessive human diseases. The charging of tRNA PHE with phenylalanine is performed by a tetrameric enzyme that contains two alpha (FARSA) and two beta (FARSB) subunits. To date, mutations in the genes encoding these subunits ( FARSA and FARSB ) have not been implicated in any human disease. Here, we describe a patient with a severe, lethal, multisystem, developmental phenotype who was compound heterozygous for FARSB variants: p.Thr256Met and p.His496Lysfs*14. Expression studies using fibroblasts isolated from the proband revealed a severe depletion of both FARSB and FARSA protein levels. These data indicate that the FARSB variants destabilize total phenylalanyl‐tRNA synthetase levels, thus causing a loss‐of‐function effect. Importantly, our patient shows strong phenotypic overlap with patients that have recessive diseases associated with other ARS loci; these observations strongly support the pathogenicity of the identified FARSB variants and are consistent with the essential function of phenylalanyl‐tRNA synthetase in human cells. In sum, our clinical, genetic, and functional analyses revealed the first FARSB variants associated with a human disease phenotype and expand the locus heterogeneity of ARS‐related human disease.